Integrating mHealth mobile applications to reduce high risk drinking among underage students. (May 2014) - Kazemi, Donna M; Cochran, Allyson R; Kelly, John F; Cornelius, Judith B; Belk, Catherine
Objective: College students embrace mobile cell phones (MCPs) as a primary communication and entertainment device. The aim of this study was to investigate college students' perceptions toward using mHealth technology to deliver interventions to prevent high-risk drinking and associated consequences. Design/setting: Four focus group interviews were conducted during the spring and fall of 2011 at a large public university in the southeastern United States of America (USA) to collect data on the applicability of mHealth technology to alcohol-prevention programmes. The participants were students currently enrolled in a face-to-face alcohol-prevention programme. Method: Thematic analysis of the content in the transcriptions was used to analyse the focus group responses using a codebook. Results: Four major themes emerged which were: (1) education and usability; (2) Skype capabilities; (3) enhanced social networking; and (4) use for tracking and feedback. All of the participants said they would join an alcohol-intervention programme that incorporated mHealth mobile technology as a primary mode of communication. Conclusions: The positive responses to the use of mobile applications indicate that use of interactive, real-time technology would be valuable to college students. Given the cost of face-to-face delivery of interventions, the findings are encouraging and support further exploration of the application of mHealth technology. Mobile technologies (mHealth) could provide a more effective delivery of alcohol-intervention programmes and increase the accessibility, relevance, and value of alcohol-intervention programmes.